A Tough Metal‐Coordinated Elastomer: A Fatigue‐Resistant, Notch‐Insensitive Material with an Excellent Self‐Healing Capacity. Issue 4 (25th April 2019) - Gai, Guangjie; Liu, Libin; Li, Cheng‐Hui; Bose, Ranjita K.; Li, Dong; Guo, Ning; Kong, Biao
Abstract: Self‐healing materials can prolong device life, but their relatively weak mechanical strength limits their applications. Introducing tunable metal‐ligand interactions into self‐healing systems can improve their mechanical strength. However, applying this concept to solid elastomers is a challenge. To address this need, polyurethane‐containing metal complexes were fabricated by introduction of a pyridine‐containing ligand into polyurethane, and subsequent coordination with Fe 2+ . The strong reversible coordination bond provides mechanical strength and self‐healing ability. By optimizing the monomer ratio and Fe 2+ content, the resulting complex possesses a very high tensile strength of 4.6 MPa at strain of around 498 % and a high Young's modulus (3.2 MPa). Importantly, the metal complex exhibits an extremely high self‐healing efficiency of approximately 96 % of tensile strength at room temperature and around 30 % at 5 °C. The complex is notch‐insensitive and the fracture energy is 76186 J/m 2, which is among the highest reported values for self‐healing systems. Abstract : Tough and stretchable : A metal‐coordinated polyurethane complex was fabricated by complexing a simple pyridine‐containing ligand with Fe 2+ ions The strong reversible coordination bond provides mechanical strength and the basis for self‐healing. The complex possesses a very high tensile strength, and excellent self‐healing efficiency of around 96 % of tensile strength at room temperature. The complex is notch‐insensitive and possesses a very high fracture energy of 76186 J/m 2 .